2012
DOI: 10.1523/jneurosci.2904-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Extracellular Volume Reveals a Neurodegenerative Pattern in Schizophrenia Onset

Abstract: Diffusion MRI has been successful in identifying the existence of white matter abnormalities in schizophrenia, in-vivo. However, the role of these abnormalities in the etiology of schizophrenia is not well understood. Accumulating evidence from imaging, histological, genetic and immunochemical studies support the involvement of axonal degeneration and neuroinflammation - ubiquitous components of neurodegenerative disorders - as the underlying pathologies of these abnormalities. Nevertheless, the current imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
304
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(328 citation statements)
references
References 57 publications
21
304
2
1
Order By: Relevance
“…Higher MD indicates poor WM organization, and increasing MD over time reflects a progressive loss of WM organization. This could be interpreted as progressive demyelination, but a neuroinflammatory response could also increase MD 22,23 and is a problematic secondary injury in TBI. 24 Excess tissue water due to inflammation can also register as an increase in MD.…”
mentioning
confidence: 99%
“…Higher MD indicates poor WM organization, and increasing MD over time reflects a progressive loss of WM organization. This could be interpreted as progressive demyelination, but a neuroinflammatory response could also increase MD 22,23 and is a problematic secondary injury in TBI. 24 Excess tissue water due to inflammation can also register as an increase in MD.…”
mentioning
confidence: 99%
“…This scenario may, at least in part, explain the previous postmortem findings of decreased dendritic spines and neuropil in subjects with schizophrenia (Garey et al 1998;Costa et al 2001;Lewis 1997, 2000;Selemon and Goldman-Rakic 1999). Of interest, consistent with this hypothesis, using a novel free-water imaging technique, it has recently been shown that the extracellular space in the cerebral cortex, of which ECM and PNNs are major components, was significantly decreased in first-episode schizophrenia patients (Pasternak et al 2012).…”
Section: Reduced Pnns May Contribute To the Dysfunction Of Pv And Pyrmentioning
confidence: 70%
“…However, more research is needed to study the role of central inflammaltion in CRPS and its relationship to DTI abnormalities. For example, neuroinflammation‐specific changes of extracellular volume are more likely to be identified with free‐water imaging which is sensitive to water diffusion in the extracellular space (Pasternak et al., 2012, 2015). …”
Section: Discussionmentioning
confidence: 99%